FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK DENGAN PREFERENSI RISIKO SEBAGAI VARIABEL MODERASI - Andreas Bambang Daryatno (Universitas Multimedia Nusantara, 2021)
Abstract - The tax target from the government has never been achieved, previous research has shown inconsistencies between researchers, and the economic sector has declined due to the COVID-19 pandemic. Whether the current state of the COVID-19 pandemic will produce consistent or inconsistent results if research is carried out on compliance with fulfilling obligations in paying taxes. The purpose of this study is to obtain empirical evidence regarding the effect of understanding tax regulations, tax sanctions, and service of tax officials on taxpayer compliance with risk preference as a moderating variable. This study used 104 samples through simple random sampling method. The data used is primary data in the form of questionnaires distributed to individual taxpayers in Jakarta. Data processing in this study using the Smart Pls3 program. The results showed that prior to moderating the understanding of tax regulations and services of tax officials had an effect on taxpayer compliance, while tax sanctions had no effect on taxpayer compliance. After moderating with the risk preference variable statistically resulted in the understanding of tax regulations, the service of the tax authorities strengthened even though it had very little effect on taxpayer compliance. Meanwhile, the tax sanctions variable could not predict positively on taxpayer compliance, meaning that the risk preference variable was not statistically proven to be able to moderate . From the empirical results above, it shows that the Directorate General of Taxes should focus more on providing education, socialization in an effort to increase the understanding of taxpayers so that awareness arises in paying taxes and participating in mutual cooperation in building the Indonesian nation to achieve mutual prosperity. Keywords: Risk Preference; Taxpayer Compliance; Tax Sanctions; Tax Service Officers; Understanding of Tax Regulations